Semiotic Analysis of “Jaranan Jowo” in Kediri (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2025)
This study aims to analyze the Jaranan Jowo performance in Kediri through a semiotic approach to uncover the symbolic meanings embedded within the performance elements such as properties, dance movements, music, and ritual systems. Jaranan Jowo is not merely a form of traditional entertainment but also serves as a medium of cultural communication that represents the spiritual, agrarian, and cosmological values of Javanese society. This research employs a qualitative method with observation, interviews, and documentation as the primary sources of data. The results indicate that each element of the performance functions as a semiotic system representing the relationship between humans, nature, ancestors, and the spiritual realm. Properties such as the kuda lumping and barongan symbolize protective forces and cosmological entities, while music and rituals act as cultural codes that reinforce the community’s social and spiritual bonds. These findings suggest that Jaranan Jowo is a rich cultural narrative embedded with symbolic messages and plays a significant role in preserving local identity amidst the pressures of globalization.